Avaliação metrológica da medição de vazão com laser doppler anemométrico - Thiago Teixeira de Paula (2007)
Laser Doppler Anemometry is a measurement system which not only contains a wide velocity measurement range (whose speed amounts to 200 m/s) and good accuracy but is also noninvasive. That is why it has increasingly been used as a primary standard for velocity in fluidsmeasurement as well as in flow measurement gauging systems. Devices used as measurement standards need traceability, which can only be assured through calibration. As a result, from LDA calibration the user gets more reliable measurements and results for the gauges,calibrated by LDA. Such calibration is mainly important for CPH, since it is used in researches and experiments both inside or outside laboratory, where fluid velocity or the flow is mostly the main variable, if not the only one. This study has had two prime aims. The former consisted of development, construction and testing a device able to calibrate the LDA,within a velocity range from 1 to 5 m/s, considering a velocity uncertainty of 0,1%, at the most, and a coverage factor of 95%. Applying this calibration device to the LDA a maximum error of 4,5% of the measured velocity was obtained. Once the systematic effects are corrected, the extended measurement uncertainty was estimated to be ±2,6% of the measured value. The second aim took into account the use of the calibrated LDA along with the right velocity and area method in order to carry out water flow measurements within a range of 11 to 26 l/s. The flow measurements were used to check on the applicability of the LDA as aprimary flow standard and raise and quantify its uncertainty sources. In the flow measurement the relative uncertainty varied from 11 through 20%, which means that the LDA itself is unsuitable as a flow primary standard.